Development of a Model for Increasing Village Government Resources Based on Recognition of Past Learning - Arief Rohman; Zaenuri Zaenuri; Nanik Wijayati; Fathur Rokhman (Universitas Negeri Semarang, 2023)
Village governments have an important role in national development, but still face various challenges in improving human and organizational resources. In addition, the village government also plays a crucial role in the management and development of rural areas. To improve the effectiveness of village government performance, it is necessary to make efforts to improve existing human resources. This study aims to develop a model for increasing village government resources based on recognition of past learning (RPL). RPL is a process of acknowledging one's competence based on formal, non-formal and informal learning experiences. This model is expected to provide incentives for village apparatus to improve the quality of public services and community participation. This study uses research and development (R&D) methods with preliminary study stages, model development, model validation, and model trials. The results showed that the developed RPL model had four main components, namely: (1) village government competency standards; (2) process of identification, documentation and verification of competency; (3) certification and award mechanisms; and (4) continuous competency development program. This model received positive responses from experts and practitioners, and had a positive impact on increasing the motivation, performance and capacity of village apparatus in trials conducted in Blora Regency, Jawa Tengah.